Short Communication: The phenology of Sonneratia alba J. Smith in Berbak and Sembilang National Park, South Sumatra, Indonesia - SARNO SARNO; RUJITO AGUS SUWIGNYO; ZULKIFLI DAHLAN; MUNANDAR MUNANDAR; MOH. RASYID RIDHO; NITA AMINASIH; HARMIDA HARMIDA; M. EDI ARMANTO; ELISA WILDAYANA (Biodiversitas Journal of Biological Diversity, 2017)
Sarno, Suwignyo RA, Dahlan Z, Munandar, Ridho MR, Aminasih N, Harmida, Armanto ME, Wildayana E. 2017. Short Communication: The phenology of Sonneratia alba J. Smith in Berbak and Sembilang National Park, South Sumatra, Indonesia. Biodiversitas 18: 909-915. The ecosystem of mangrove forms the largest portion of the habitat in Berbak and Sembilang National Park (BSNP), Banyuasin District, South Sumatra Province, Indonesia, which is the largest mangrove area in the western part of Indonesia. There is a tendency that the mangrove condition in this area is gradually degrading over time. The main causes of mangrove destructions are both natural and human factors. The destructions of mangrove in BSNP directed by human are more than natural factors, for axample, land use conversion from wildland into cultivated land, the making of ponds, especially along Banyuasin Peninsula. The information on the observation of mangrove phenology is very important for sustainable mangrove management. The observation of mangrove phenology in the restoration area of BSNP is intended to study the natural stages of growth and reproductive development of Sonneratia alba J. Smith, the local name is Padada. The observation is done by means of tagging methods. Monitoring is conducted periodically from the flowering time until the fruit was ripe. The phenology of Sonneratia alba takes about three months from the beginning of flowering until the fruit was ripe.